EVALUATION OF SOCIALIZATION PROGRAMS AND PROMOTIONS OF OPEN UNIVERSITY IN INCREASING PARTICIPATION OF UPBJJ-UT MATARAM NEW STUDENTS - Nining Suryani; Windi Baskoro Prihandoyo; Khaerul Anam; Gunawan Wiradharma (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This study aims to determine the effectiveness of socialization and promotion strategies in increasing student participation rates at UT Mataram. The method used in this research is correlational descriptive survey method. The results of this study are: 1. The target target of the socialization and promotion program in the future by utilizing information technology as a promotional media, 2. The number of respondents who know about UT is 101 people or 77.7%, while respondents who do not know about UT are as many as 101 people. 29 people or 22.3% indicates that the dissemination of information about UT in the NTB region is still not optimal. 3. The effectiveness of the social program has an impact on increasing student participation rates. Then sosprom activities in the period 2019.2 can be used as a reference for the activity stage in the next period